The Assessment of Kalare Eradication Policies in Nigeria: A Study of Anti Kalare Squad and Talba Empowerment Scheme (TES) - Mohammed Umar, Bashir; Kamsiah, Ali; Lucy, Sebli Siedelson (Quest Journals, 2017)
: Government or public policies are policies that are made at different times and in most cases by different governmental organizations. This can be at the federal, state and at the local levels through which the governments advance and make meaningful economic and human developments. Gombe state government in Eastern Northern Nigeria in its response to the numerous complaints by its citizens over the political violence activities perpetrated by youth groups known as Kalare in the state has formulated two policies with the intention to eradicate these violence activities. These policies include Anti Kalare Squad and Talba Empowerment Scheme (TES) but unfortunately these policies achieved limited success especially in eradicating the violent activities perpetrated by the youth. Hence, this paper assessed the factors responsible for the limited success of the two policies. The findings of this paper revealed that the implementation of these policies was marred by political interference influenced by personal interest and political sentiments. The study recommends that a monitoring and evaluation and mediating committees should be set up which will function as mediator among the different Kalare groups to ensure proper implementation of the policies. Keywords:- Assessment, Kalare, Eradication, Policies, Gombe state